Experimentally induced anti-myeloperoxidase vasculitis is not attenuated in factor B or VISTA deficient mice - Fernanda Flórez-Barrós (Karger Publishers, 2021)
Background: Anti-neutrophil cytoplasmic antibody vasculitis is characterised by antibodies to myeloperoxidase or proteinase 3. Previous work in murine anti-myeloperoxidase vasculitis has shown a role for the alternative pathway complement component factor B and the anaphylotoxin C5a. However, mice deficient in properdin, which stabilizes the alternative pathway convertase, were not protected. VISTA-deficient mice were protected in the nephrotoxic nephritis model but the role of VISTA in anti-myeloperoxidase vasculitis is unknown. Objectives: This study had two aims. Firstly, we attempted to reproduce previous findings on the role of factor B in anti-myeloperoxidase vasculitis. Secondly, we examined the role of VISTA in this model, in order to see if the protection in the nephrotoxic nephritis model extended to anti-myeloperoxidase vasculitis. Methods: Anti-myeloperoxidase vasculitis was induced in wildtype, factor B, or VISTA deficient mice. Disease was assessed by quanitfying glomerular crescents and macrophages, in addition to albuminuria and serum creatinine. Results: When wild type and factor B deficient mice were compared, there were no differences in any of the histological or biochemical parameters of disease assessed. Similarly, when wild type or VISTA defiicent mice were compared, there were no differences. Conclusions: Factor B deficient mice were not protected which is in contrast to previous studies. Therefore alternative pathway activation is not essential in this model, under the conditions used in this study. VISTA deficient mice were not protected, suggesting that therapies targetting VISTA may not be effective in vasculitis.